Recent Progress in Ionic Liquids for Stability Engineering of Perovskite Solar Cells. Issue 8 (31st May 2022) - Wang, Fei; Ge, Chuang-ye; Duan, Dawei; Lin, Haoran; Li, Liang; Naumov, Panče; Hu, Hanlin
Abstract : Perovskite solar cells attract widespread attention due to their impressive power conversion efficiencies, high absorption coefficients, tunable bandgap, and straightforward manufacturing protocols. However, in the process of further development and optimization toward mass production, the long‐term stability stands as one of the most urgent challenges that need to be overcome. Given the excellent thermal stability and high structural designability, ionic liquids (ILs) are relatively green room‐temperature molten salts that have been widely applied to perovskite photovoltaic devices with promising results in view of improved stability and enhanced device performance. In this review, the reasons and mechanisms of instability of such devices under external and internal factors are analyzed. The current strategies of ILs engineering for improved stability of the devices are classified and summarized, including the IL‐assisted perovskite film evolution and IL‐modified photophysical properties of the perovskite photoactive layer and the related stability and photovoltaic performance of the devices. The challenges that stand as obstacles toward further development of perovskite solar cells based on IL engineering and their prospects are also discussed. Abstract : Aiming to address the problem of stability of perovskite solar cells, this review summarizes different mechanisms for improving device stability based on the application of ionic liquids. Strategies for introduction of hydrophobic groups, defect reduction, and formation of chemical interactions for stability engineering are analyzed and discussed.